ANALISIS KADAR ION LOGAM TIMBAL (Pb2+) PADA AIR, IKAN PATIN (Pangasius pangasius), IKAN MAS (Cyprinus carpio L.) DAN IKAN NILA (Oreochromis sp.) DI DANAU BEKAS GALIAN TAMBANG BATUBARA KECAMATAN TENGGARONG SEBERANG - Recha Defrosa Morasih Samta Sihotang; Saibun Sitorus; Rahmat Gunawan (PROSIDING SEMINAR KIMIA, 2017)
An Analysis of Lead Metal Ion Levels (Pb2+) has been conducted on water, Cat fish (Pangasius pangsius), Gold fish (Cyprinus carpio L) and Parrot fish (Oreochromis sp.) in abandoned coal mine lake in Tenggarong Seberang sub-district. This research was intended to determine the Pb metal ion levels inside water and fish also to understand its appropriateness to be consumed by humans. This research was done with using destruction method on the woven basket water sample and fish’s meat sample (Catfish, Goldfish, and Parrotfish) and then proceed the analyzed using Atomic Absorption Spectrophotometer (AAS). Pb levels acquired in this research are 0,039 in Parrot fish woven basket, 0,031 ppm in Goldfish woven basket that exceeds the quality standards threshold according to PP RI No. 82 Tahun 2001, dissimiliar with Pb levels in Catfish woven basket in the amount of 0,016 ppm which is still far below the threshold. While the Pb levels in all three fishes are under standard quality threshold according to SNI 7387:2009 about maximum limit of heavy metal contamination inside foods, where the levels in Parrot fish is 0,138 ppm, goldfish meat as 0,060 ppm and catfish meat as 0,041 ppm. Keywords: Parrot fish, Goldfish, Catfish, Pb levels, Threshold